1994
DOI: 10.1152/jn.1994.72.5.2420
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosensitive properties of pelvic nerve afferent fibers innervating the urinary bladder of the rat

Abstract: 1. Single-unit activity was recorded from S1 dorsal root afferent fibers in pentobarbital-anesthetized rats. In 25 experiments, 245 afferent fibers were identified by electrical stimulation of the pelvic nerve. Fifty-two percent were C fibers (conduction velocity: 1.70 +/- 0.04 m/s; mean +/- SE) and 48% were A delta-fibers (conduction velocity: 11.07 +/- 0.95 m/s). 2. Of 245 pelvic nerve afferent fibers, 92 (38%) responded to noxious urinary bladder distension (UBD; 80 mmHg); 57 of these fibers were C fibers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
165
3
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(190 citation statements)
references
References 0 publications
21
165
3
1
Order By: Relevance
“…Most LS bladder neurons were small or medium in size based on capacitance, a finding consistent with an immunohistochemical study of S1 bladder neurons (Yohimura et al, 2003) and electrophysiological evidence that 50 -70% of pelvic nerve bladder afferents conduct in the C-fiber range (Sengupta and Gebhart, 1994;Shea et al, 2000). In contrast, we found that TL bladder neurons were medium to large in size, although Ͼ90% of hypogastric/lumbar splanchnic nerve fibers are unmyelinated based on conduction velocity (Nadelhaft and Vera, 1991).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Most LS bladder neurons were small or medium in size based on capacitance, a finding consistent with an immunohistochemical study of S1 bladder neurons (Yohimura et al, 2003) and electrophysiological evidence that 50 -70% of pelvic nerve bladder afferents conduct in the C-fiber range (Sengupta and Gebhart, 1994;Shea et al, 2000). In contrast, we found that TL bladder neurons were medium to large in size, although Ͼ90% of hypogastric/lumbar splanchnic nerve fibers are unmyelinated based on conduction velocity (Nadelhaft and Vera, 1991).…”
Section: Discussionsupporting
confidence: 90%
“…Thus, IB4-positive neurons comprised 48.8 Ϯ 2.5% (n ϭ 3) and 54.3 Ϯ 3.8% (n ϭ 3) of all LS and TL DRG neurons in the samples studied, respectively ( p Ͼ 0.05). Approximately 50 -70 and 96% of rat bladder pelvic and hypogastric/splanchnic afferents, respectively, have slow conduction velocities consistent with the absence of myelination (Nadelhaft and Vera, 1991;Sengupta and Gebhart, 1994;Shea et al, 2000). To characterize bladder sensory neurons further, we applied IB4 after examination of neurons as described above (Fig.…”
Section: Ib4 Labelingmentioning
confidence: 99%
“…Similar findings were also noted by Berkley et al, (1990), and most recently, by Malykhina et al, (2004) who have also begun physiologically characterizing dually-labeled DRG neurons projecting to both the bladder and colon. Sengupta and Gebhart (1994) reported no evidence of individual sacral dorsal root afferents responding to distension of both the colon and bladder, however it is possible that afferents innervating more than one organ are either not responsive to mechanical stretch (e.g. they are mucosal or serosal afferents (Brierley et al 2004)) or that they are "silent" nociceptors, which become mechanically-sensitive following inflammation or other insult.…”
Section: Discussionmentioning
confidence: 99%
“…In rats, Sengupta and Gebhart (561) reported that both Aδ-and C-fiber afferents are mechanosensitive and respond to bladder distension (Fig. 2B).…”
Section: Afferent Innervationmentioning
confidence: 98%
“…Chronic conditions that involve continuous tissue inflammation or irritation can induce changes in sensory pathways that lead to hyperalgesia (heightened response to painful stimuli) and allodynia (pain in response to normally nonpainful stimuli). Thus, continuous tissue inflammation in visceral organs such as the bladder can lead to sensitization of afferent nerves and increased afferent nerve responses to both noxious and nonnoxious stimuli (251,561). In a rat model of chronic cystitis induced by cyclophosphamide or hydrochloric acid, it has been shown that capsaicin-sensitive bladder afferent neurons increase their excitability due to decreased density of A-type K + (K A ) currents, associated with the decreased expression of the Kv1.4 α-subunit (260,703).…”
Section: Inflammation/bladder Pain Syndromementioning
confidence: 99%